Tequila sunrise [videorecording (DVD)] - Towne, Robert; Gibson, Mel; Pfeiffer, Michelle, 1957-; Russell, Kurt; Julia, Raul (Warner Home Video, 1997)
Mac McKussic has decided to quit the drug-smuggling business, but it won't quit him. Nick Frescia, the cop assigned to reel in boyhood pal Mac, and a sexy restaurateur make for sexy, tough, volatile thriller. Conspiracy theory: New York cab driver and conspiracy buff Jerry Fletcher tells anyone in earshot about the secret movers, shakers and assassins who really control things. When he tries to put Justice Department attorney Alice Sutton in the know, he's run out of her office. Soon both will be running for their lives.